1953
DOI: 10.1128/jb.65.3.313-317.1953
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Chloromycetin and Related Compounds by Escherichia Coli

Abstract: Smith and Worrel (1949, 1950b) have demonstrated that the nitro group of chloromycetin is essential for the antibiotic properties of the drug. Bacterial reduction of the nitro group results in lose of bacteriostatic action and enables

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1953
1953
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The nitro group of CAP is the essential functional group determining its antibiotic properties. , The CAP toxicity can be effectively mitigated by anaerobic transformation of the nitroaromatics to aromatic amines, with the latter being less toxic and considerably easier to be mineralized than the former. Dehalogenation generally makes halogenated compounds less toxic and more readily biodegradable . Physical-chemical methods such as photocatalytic degradation, Fenton process, zerovalent bimetallic nanoparticles and microwave radiation were proposed for CAP removal at the expense of high energy and chemical costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitro group of CAP is the essential functional group determining its antibiotic properties. , The CAP toxicity can be effectively mitigated by anaerobic transformation of the nitroaromatics to aromatic amines, with the latter being less toxic and considerably easier to be mineralized than the former. Dehalogenation generally makes halogenated compounds less toxic and more readily biodegradable . Physical-chemical methods such as photocatalytic degradation, Fenton process, zerovalent bimetallic nanoparticles and microwave radiation were proposed for CAP removal at the expense of high energy and chemical costs.…”
Section: Introductionmentioning
confidence: 99%
“…14−16 The nitro group of CAP is the essential functional group determining its antibiotic properties. 17,18 The CAP toxicity can be effectively mitigated by anaerobic transformation of the nitroaromatics to aromatic amines, with the latter being less toxic and considerably easier to be mineralized than the former. 19−21 Dehalogenation generally makes halogenated compounds less toxic and more readily biodegradable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chloramphenicol reduction activity in the originating organism (“native host”), in Es. coli expressing the gene (“heterologous”), or in an enzymatic assay (“ in vitro ”) is indicated to the right, with dark boxes indicating significant activity and white boxes indicating no activity detected (see Table S4 in the supplemental material for corresponding citations 9 , 11– 12 , 15 17 , 56 ); nd, corresponds to data that are not available.…”
Section: Discussionmentioning
confidence: 99%
“…1a ). Reduction of chloramphenicol to amino-chloramphenicol has been reported in a variety of bacterial strains ( 9 12 ) and has contributed to treatment failure in an animal model that used this antibiotic ( 13 ). Reduction of the chloramphenicol nitro group has also been hypothesized to underlie the serious chloramphenicol side effect of aplastic anemia, and prolonged exposure has also been associated with renal toxicity ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The series of investigations which have been carried out on the bacterial decomposition of the drug has revealed that bacteria may use several reactions to convert the antibiotic into compounds which will no longer inhibit the growth of the organism (75,77,78,79,80,81). It has been shown that the amide group (80).…”
Section: Downloaded Frommentioning
confidence: 99%